Genetic architecture and association study of yield and component traits of sesame (Sesamum indicum L.) genotypes: Genetic architecture and association study of yield and component traits of sesame (Sesamum indicum L.) genotypes - RAJANI BISEN; ROSHNI SAHU; A K PANDAY; K N GUPTA; SURABHI JAIN; VINOD K GOYAL; PIYUSH UPADHYAY (Journal of Oilseeds Research, 2023)
In the present experiment, 328 sesame genotypes were evaluated in Summer season 2021 with augmented block design at Project Coordinating Unit (Sesame and Niger), JNKVV, Jabalpur. Twelve quantitative traits were taken into consideration where significant variability was obtained for all the studied traits. The significant positive correlation was observed for primary branches/plant, secondary plant/plant, node to first flower, seed/capsule, capsule length, capsule/plant and plant height with seed yield/plant. On the basis of PCA, 5 PCs obtained more than one eigen value. Overall results revealed that traits and genotypes studied have a considerable level of variability which can be exploited in future breeding programmes.